2021
DOI: 10.1108/hff-01-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

Double-diffusive convection of a nanofluid in a porous cavity containing rotating hexagon and circular cylinders: ISPH simulations

Abstract: Purpose The purpose of this study is to apply an incompressible smoothed particle hydrodynamics (ISPH) method to simulate the Magnetohydrodynamic (MHD) free convection flow of a nanofluid in a porous cavity containing rotating hexagonal and two circular cylinders under the impacts of Soret and Dufour numbers. Design/methodology/approach The inner shapes are rotating around a cavity center by a uniform circular motion at angular rate ω. An inner hexagonal shape has higher temperature Th and concentration Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Exceptional work on Dufour and Soret phenomena on hydrology and petrology consist of doubled alloys solidification, isotope separation, chemical reactors, pollutant migration of groundwater, and multi-component melts. Aly and Raizah 25 scrutinized the MHD free convection flow on the nanofluid by the permeable cavity containing two circular cylinders and rotating hexagonal below the effects on Dufour and Soret numbers. Lee et al 26 have considered thermophoretic microfluidic cells for studying the Soret coefficient to colloidal particles.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional work on Dufour and Soret phenomena on hydrology and petrology consist of doubled alloys solidification, isotope separation, chemical reactors, pollutant migration of groundwater, and multi-component melts. Aly and Raizah 25 scrutinized the MHD free convection flow on the nanofluid by the permeable cavity containing two circular cylinders and rotating hexagonal below the effects on Dufour and Soret numbers. Lee et al 26 have considered thermophoretic microfluidic cells for studying the Soret coefficient to colloidal particles.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the presence of blades has a positive effect on the process under study. Aly and Raizah (2022) have studied the free convection of a nanofluid in a square porous cavity containing rotating hexagonal and two circular cylinders, under the influence of Soret and Dufour phenomena. The hexagonal porous insert has a higher temperature than the cylindrical ones.…”
Section: Introductionmentioning
confidence: 99%